2015
DOI: 10.1111/cen3.12267
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to glycoconjugates in autoimmune neuropathies

Abstract: In glycoconjugates, the most likely targets for autoantibodies in such autoimmune neuropathies are glycolipids, especially N-acetylneuraminic acid-bearing glycosphingolipids termed gangliosides. Antiganglioside antibodies are often associated with clinical phenotypes. This association depends on the diverse distribution of gangliosides in the peripheral nervous system. Complement activation is the main mechanism of antiganglioside antibody-mediated nerve injury in Guillain-Barr e syndrome. Complement-independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…FCGR has previously been identified in SCs, which may aid in the regulation of the immune response ( 35 ). A recent study reported that FCGR had a potential role in axonal injury through the mediation of inflammation ( 36 ). RAC2 has been previously identified as stimulating AKT activation in primary mast cells ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…FCGR has previously been identified in SCs, which may aid in the regulation of the immune response ( 35 ). A recent study reported that FCGR had a potential role in axonal injury through the mediation of inflammation ( 36 ). RAC2 has been previously identified as stimulating AKT activation in primary mast cells ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, in sera from patients with C . jejuni ‐associated GBS, levels of immunoglobulin G (IgG) autoantibodies against various gangliosides (GM1, GM1b, GD1a and GalNAc‐GD1a) are transiently increased during the acute phase of the illness . Mass spectrometry analyses showed that sugar sequences identical to those of GM1 and GD1a are expressed on the lipo‐oligosaccharide (LOS) of the C .…”
Section: Jejunimentioning
confidence: 99%
“…Briefly, in sera from patients with C. jejuni-associated GBS, levels of immunoglobulin G (IgG) autoantibodies against various gangliosides (GM1, GM1b, GD1a and GalNAc-GD1a) are transiently increased during the acute phase of the illness. 6 Mass spectrometry analyses showed that sugar sequences identical to those of GM1 and GD1a are expressed on the lipo-oligosaccharide (LOS) of the C. jejuni strains isolated from GBS patients. [28][29][30] On sensitization with GM1-like C. jejuni LOS isolated from a GBS patient, rabbits developed acute motor axonal neuropathy with anti-GM1 IgG antibodies that resembled with human C. jejuni-associated GBS.…”
Section: Jejunimentioning
confidence: 99%
See 2 more Smart Citations